Cervical Spondylotic Myelopathy—Diagnostics and Clinimetrics - Józef Opara; Martyna Odzimek (Diagnostics, 2024)
Cervical myelopathy is referred to in many ways in the English literature, for example, as cervical spondylotic myelopathy (CSM), spondylotic radiculomyelopathy (SRM) or degenerative cervical myelopathy (DCM). In addition, more frequent occurrences are noted in older adults and to a greater extent in men. The causes of the effects of cervical myelopathy may be the appearance of lesions on the spinal cord, ischemia due to compression of the vertebral artery and repeated micro-injuries during maximal movements—hyperflexion or hyperextension. It is well known that lesions on the spinal cord may occur in a quarter of the population, and this problem is clearly noted in people over 60 years old. The symptoms of SCM develop insidiously, and their severity and side (unilateral or bilateral) are associated with the location and extent of spinal cord compression. Neurological examination most often diagnoses problems in the upper limbs (most often paresis with developing hand muscle atrophy), pyramidal paralysis in one or both lower limbs and disorders in the urinary system. To make a diagnosis of CSM, it is necessary to perform MRI and neurophysiological tests (such as EMG or sensory and/or motor-evoked potentials). The use of appropriately selected scales and specific tests in diagnostics is also crucial. This narrative review article describes the latest knowledge on the diagnosis and clinimetrics of cervical spondylotic myelopathy in adults and provides future directions.